Molecular modeling and in vitro studies of gedunin a potent alpha-amylase inhibitor and alpha-glucosidase inhibitor - Dagar P.; Mishra A. (My University, 2025)
The present study explores the potential of the Azadirachta indica (Neem) plant parts (stem and bark) component gedunin for inhibition of alpha-amylase and alpha glucosidase. In contrast, Methanol at 50 mg/ml and 65 mg/ml had the lowest IC50 in alpha glucosidase and alpha amylase with noncompetitive and mixed inhibition, respectively. Azadirachta indica seeds collected from ICAR showed anti-diabetes activity in vitro and in vivo seeds collected were subjected to soxhlet and nonsoxhlet techniques followed by chromatography. HR-LCMS, HPLC, and FTIR to comprehend phytoconstituents present in the extract were used to comprehend phytoconstituents present in the extract and showed the presence gedunin. Among many hits observed, gedunin was used for docking studies using ICM software and for molecular dynamic simulation using gromacs. The results show significant alpha-amylase inhibitory activity and alpha glucosidase inhibitory activity and interaction of ligand targeting these enzymes, which can be used for cross-validation, in vitro using ligplot maps and visualization. © 2022 International Union of Biochemistry and Molecular Biology.